New and old roles of the peripheral and brain renin–angiotensin–aldosterone system (RAAS): Focus on cardiovascular and neurological diseases. (15th January 2017) - Mascolo, A; Sessa, M; Scavone, C; De Angelis, A; Vitale, C; Berrino, L; Rossi, F; Rosano, G; Capuano, A
Abstract: It is commonly accepted that the renin–angiotensin–aldosterone system (RAAS) is a cardiovascular circulating hormonal system that plays also an important role in the modulation of several patterns in the brain. The pathway of the RAAS can be divided into two classes: the traditional pathway of RAAS, also named classic RAAS, and the non-classic RAAS. Both pathways play a role in both cardiovascular and neurological diseases through a peripheral or central control. In this regard, renewed interest is growing in the last years for the consideration that the brain RAAS could represent a new important therapeutic target to regulate not only the blood pressure via central nervous control, but also neurological diseases. However, the development of compounds able to cross the blood–brain barrier and to act on the brain RAAS is challenging, especially if the metabolic stability and the half-life are taken into consideration. To date, two drug classes (aminopeptidase type A inhibitors and angiotensin IV analogues) acting on the brain RAAS are in development in pre-clinical or clinical stages. In this article, we will present an overview of the biological functions played by peripheral and brain classic and non-classic pathways of the RAAS in several clinical conditions, focusing on the brain RAAS and on the new pharmacological targets of the RAAS. Highlights: Brain RAAS could represent a new important therapeutic target to regulate cardiovascular and neurological diseases. Aminopeptidase type A inhibitors and angiotensin IV analogues are new drug classes acting on the brain RAAS. The development of compounds able to cross the blood-brain barrier is challenging due to the pharmacokinetic characteristics.